2016
DOI: 10.1088/1674-1056/25/1/014701
|View full text |Cite
|
Sign up to set email alerts
|

Analytical study of Cattaneo–Christov heat flux model for a boundary layer flow of Oldroyd-B fluid

Abstract: We investigate the Cattaneo-Christov heat flux model for a two-dimensional laminar boundary layer flow of an incompressible Oldroyd-B fluid over a linearly stretching sheet. Mathematical formulation of the boundary layer problems is given. The nonlinear partial differential equations are converted into the ordinary differential equations using similarity transformations. The dimensionless velocity and temperature profiles are obtained through optimal homotopy analysis method (OHAM). The influences of the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…The investigation of the heat transfer in a fluid governed by Cattaneo-Christov heat flux model is expanding. Some of the work done are shown in [8][9][10][11].…”
Section: Fig 1: Geometry Representation Of the Fluidmentioning
confidence: 99%
“…The investigation of the heat transfer in a fluid governed by Cattaneo-Christov heat flux model is expanding. Some of the work done are shown in [8][9][10][11].…”
Section: Fig 1: Geometry Representation Of the Fluidmentioning
confidence: 99%
“…The salient characteristics of such fluids cannot be described through a constitutive relationship. Therefore, various flow models [1][2][3][4][5][6][7][8][9] have been presented in past decades to analyze significance characteristics of non-Newtonian fluids.…”
Section: Introductionmentioning
confidence: 99%
“…They proved that when the suction/injection parameter rises, then the velocity of the fluid abates strikingly along the u component of velocity, whereas the converse behavior is computed for the v component of velocity. Abbasi and colleagues studied the Cattaneo–Christov heat flux model for a laminar boundary layer flow of an incompressible Oldroyd‐B fluid over a linearly stretching sheet. They reported that the temperature and the thermal boundary layer thickness are smaller in the Cattaneo–Christov heat flux model than those in Fourier's law of heat conduction.…”
Section: Introductionmentioning
confidence: 99%